The neuroanatomy of Broca's aphasia - Pracar, Alexis L.; Biondo, Nicoletta; Dronkers, Nina F.; Ivanova, Maria V. (Frontiers in Language Sciences, 2025)
IntroductionBroca's aphasia, a condition characterized by nonfluent speech and difficulty with language production, results from focal brain damage and is most often caused by stroke. Although traditionally linked to lesions in Broca's area (Brodmann areas 44 and 45 in the left inferior frontal gyrus), recent evidence suggests that the neuroanatomy of Broca's aphasia is far more complex, implicating a broader network of cortical and subcortical regions. This study aimed to delineate the specific cortical and white matter features that, when damaged, lead to persistent Broca's aphasia.Methods39 chronic cases of Broca's aphasia and 41 cases of stroke survivors whose language functions returned to within normal limits (WNL) were included. Lesion analyses and disconnection mapping were conducted using the Brainnetome Atlas and the Lesion Quantification Toolkit (LQT).ResultsResults highlighted the critical role of the left insula, particularly its hypergranular and dorsal granular regions, which showed 99.2% and 93.6% lesion overlap, respectively, in Broca's aphasia cases. These regions, along with portions of the motor cortex and the parietal and temporal lobes, contribute to speech production and language processing. Importantly, the traditionally defined Broca's area showed minimal overlap, challenging the conventional understanding of its role in chronic Broca's aphasia. In addition to cortical regions, white matter tract analysis revealed complete disconnection of key pathways, including the arcuate fasciculus, extreme capsule, and middle longitudinal fasciculus. The corticospinal tract and inferior fronto-occipital fasciculus (IFOF) were also heavily disrupted, suggesting that damage to both cortical areas and their structural connections contributes to the hallmark symptoms of Broca's aphasia.DiscussionThese findings emphasize the distributed nature of the neural network underlying Broca's aphasia, extending beyond traditional Broca's area to include multiple cortical regions and their associated white matter tracts. The study provides new insights into the structural basis of language impairment, offering a more nuanced understanding of Broca's aphasia.